Homo reciprocans: survey evidence on prevalence, behavior and success - Thomas Dohmen; Armin Falk; David Huffman; Uwe Sunde (Institute for the Study of Labor (IZA), 2006)
Experimental evidence has convincingly shown the existence of reciprocal inclinations, i.e., a tendency for people to respond in-kind to hostile or kind actions. Little is known, however, about: (i) the prevalence of reciprocity in the population, (ii) individual determinants of reciprocity, (iii) the correlation between positive and negative inclinations within person, and (iv) consequences of reciprocal inclinations for wages, subjective well-being, friendships and other economic and social outcomes. Answering these questions requires moving out of the lab and using a large and representative subject pool, which combines information about subjects' reciprocal inclinations with extensive socioeconomic background information. In this paper we measure the reciprocal inclinations of 21,000 individuals. We show that most people state reciprocal inclinations, in particular in terms of positive reciprocity. However, there is substantial heterogeneity in the degree of reciprocity, and quite surprisingly, only a weak correlation between positive and negative reciprocity for an individual. In terms of determinants, being female, and increasing age, lead to greater positive and less negatively reciprocal tendencies. Taller people are more positively reciprocal, but height has no impact on negative reciprocity. The asymmetric impact of these determinants provides further indication that positive and negative reciprocity are fundamentally different traits, rather than the outcome of a single underlying tendency. In terms of economic implications, we provide the first evidence using a large representative survey that corroborates an important hypothesis arising from laboratory experiments: Positively reciprocal workers are in fact paid more, and exert greater effort, on the job. Moreover, positively reciprocal people are more likely to be employed, report having more close friends, and have a higher overall level of life satisfaction. In this sense, Homo Reciprocans - in the positive domain - is in fact more successful than his or her non-reciprocal fellows.
Keywords: D63; J3; J6; 330; reciprocity; trust; SOEP; wage regression; unemployment; happiness; Verhaltensökonomik; Psychologie; Arbeitszufriedenheit; Lohnniveau; Panel; Deutschland